PENGARUH PENYAJIAN LAPORAN KEUANGAN, KARAKTERISTIK KUALITATIF, AKSESIBILITAS DAN PENGENDALIAN INTERNAL TERHADAP TRANSPARANSI LAPORAN KEUANGAN PEMERINTAH DAERAH - Nurlaila Yuliani (Jurnal Bisnis dan Ekonomi, 2017)
This study is aimed at examining the effect of financial statement presentation, qualitative characteristics, accessibility and internal control on financial reporting transparency of local government at SKPD in Magelang regency. The main background of this research is motivated by empirical studies on transparency which are still diverse and growing importance of local governments in realizing good governance with transparency and accountability of financial reports. The research sample consisted of 87 employees of the finance department consisted of staffs and part of Renmonevlap at SKPD in Magelang regency. This study provides evidence that the qualitative characteristics and internal share positive effects of financial report transparency in Magelang regency. Meanwhile accessibility and presentation of financial statements do not provide positive effects on the transparency of local government financial reports. Keywords: presentation of financial reports, qualitative characteristic, accessibility, internal controls, transparency of local government financial reports.